Far eastern private libraries: preservation and investigation - N. V. Radishauskayte (Библиосфера)
Personal libraries are an important element of national and regional book culture. Their study helps to reveal similarities and peculiarities in spiritual, cultural and socioeconomic development of different regions of a country.The purpose of the article: to analyze the document flow of the Far Eastern authors, to determine the degree of study of pre-revolutionary personal libraries of the Far Eastern regions in Russia and the problems arising in their study and preservation. As a result, the content analysis revealed 33 publications on the subject for the period 1978-2017, 24 of them were published from 2001 to 2017.Conclusions: up to now there is no a complete list of owners of private libraries, their descriptions, views on the traditions of book-gathering in the region during the period men. This situation is fraught with the loss of a significant part of this segment of cultural heritage. This process can be stopped by the intensification of the identification, allocation and study of pre-revolutionary personal libraries of the far East in the book collections of institutions in the region, as well as the creation of an electronic resource that would accumulate data on the phenomenon under consideration.